KETERATURAN ANC TERHADAP PERSALINAN NORMAL - Sari, Anjelina Puspita; Romlah, Romlah; Sartika Silaban, Titin Dewi (SEKOLAH TINGGI ILMU KESEHATAN INDRAMAYU, 2024)
An indicator of improved health is the occurrence of maternal mortality rate (MMR). MMR is the prevalence of an annual number of deaths for every woman who gives birth. Data from the sampling registration system shows that 76% of maternal deaths occur during labor and postpartum phases. Many factors affect or cause complications in every childbirth which results in maternal death, therefore the government has made several programs, one of which is improving the health of pregnant women. This study aims to determine the relationship of ANC regularity to normal labor. This study used obsevational analytic research with cross sectional design. The sampling technique in this study was total sampling, with a total sample size of 50 respondents. Data was taken by retrospective data observation, namely by taking the respondent's medical records. Analysis in this study using the Chi-Square test. The statistical test results showed that there was a significant relationship between ANC regularity and normal labor with a p-value = 0.003. The conclusion in this study is that regularity of antenatal care affects the type of labor that will be performed in each mother. It is recommended that pregnant women should routinely make ANC visits in order to maintain their normality until labor, postpartum and breastfeeding